2013
DOI: 10.1016/j.otsr.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Distal femur fractures. Surgical techniques and a review of the literature

Abstract: Fractures of the distal femur are rare and severe. The estimated frequency is 0.4% with an epidemiology that varies: there is a classic bimodal distribution, with a frequency peak for men in their 30s and a peak for elderly women; however, at present it is found predominantly in women and in the elderly with more than 50% of patients who are over 65. The most common mechanism is an indirect trauma on a bent knee, and more rarely direct trauma by crushing. The anatomy of the distal femur explains the three majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(145 citation statements)
references
References 37 publications
1
134
0
10
Order By: Relevance
“…Because these descriptors are not present in the NSQIP database, it is difficult to validate the direct comparison of patients undergoing these two procedures for DF fractures. 19 The small number of IMN cases in this study makes it difficult to draw final conclusions about the observed differences between treatment groups. The classification of DF fractures in NSQIP based on ICD-9 codes cross-referenced with CPT codes impeded a larger selection of cases.…”
Section: S197mentioning
confidence: 82%
“…Because these descriptors are not present in the NSQIP database, it is difficult to validate the direct comparison of patients undergoing these two procedures for DF fractures. 19 The small number of IMN cases in this study makes it difficult to draw final conclusions about the observed differences between treatment groups. The classification of DF fractures in NSQIP based on ICD-9 codes cross-referenced with CPT codes impeded a larger selection of cases.…”
Section: S197mentioning
confidence: 82%
“…введение повреждения бедренной кости составля-ют 15-45% в общей структуре переломов [1]. Однако переломы дистального отдела бедрен-ной кости встречаются относительно редко -их частота варьирует от 0,4 до 7% от всех пе-реломов бедренной кости [2][3][4][5][6]. по данным B.D.…”
Section: Discussionunclassified
“…Anatomical design of plate allow it to use as reduction mould, molding bone to the plate. 4 Definitive treatment of distal femur fracture require maintaining or restoring distal femoral alignment to preserve functions of extremity. Early knee motion is required in achieving good range of movement.…”
Section: 13mentioning
confidence: 99%
“…[1][2][3] A classic bimodal distribution exist with one peak in incidence in young men (15-30 years) and elderly women (>70 years). 4,5 Young patients are affected by high velocity trauma(including motor vehicle accident, motorcycle or sports injury) and elderly are predisposed to low energy fracture due to osteoporosis. 3,6 Although not as common as femoral shaft or hip fractures, fractures of the distal femur are complex injuries and difficult to manage.…”
Section: Introductionmentioning
confidence: 99%